Convergent validity of True Colors™ Character Cards' Activity and Word Cluster Instrument with the Myers Briggs Type Indicator, Strong Interest Inventory, and Campbell Interest and Skill Survey - Honaker, Stevie L., author; Feller, Richard, advisor; Rouner, Donna, committee member; Davies, Timothy Gray, committee member; Cobb, R. Brian, committee member (Colorado State University. Libraries, 2001)
With the increased use of the True Colors™ nationally over the last twenty years to date, no manual detailing any psychometric properties has been produced. The purpose of this research was to conduct a convergent validity study of the True Colors™ Character Cards' Activity and Word Cluster Instrument using: the Myers-Briggs Type Indicator (MBTI), Form G, the Strong Interest Inventory (SII), and the Campbell Interest and Skill Survey (CISS). Subjects completing the 4 assessments consisted of 56 students enrolled in a graduate-level human resource program. Data analyses included one-way ANOVAs, t-test for independent samples, Levene's test for equality of variances, and Spearman Rank Order and Pearsons Product Moment correlations. Results of the correlations support the convergent validity of True Colors™ Character Cards' Activity and Word Cluster Instrument with the MBTI. However, little support was found for True Colors™ convergent validity with the SII and CISS. Gender differences had no effect on the True Colors™ results. However, gender did prove to effect the Thinking - Feeling dimension of the MBTI. The SII's gender differences were with the Realistic and Enterprising General Occupational Themes. Finally, the CISS's gender differences were with the Creating and Adventuring Orientations. One implication from this study is that True Colors™ has significant relationships with the MBTI and provides information on how True Colors™ specifically relates to it; however, these relationships do not always follow logical assumptions a professional who has knowledge of both the MBTI and True Colors™ might make. Thus, the findings underscore the need for caution in extrapolating types across different personality assessments. Also provided is practical application information for using the True Colors™ Character Cards' Activity and Word Cluster Instrument in regard to the fact that these different tools each have an appeal to specific personality types and illicit a participant's confidence and responses differently. The Character Cards' Activity appeals most to Blue and Orange personalities and attracts creative and artistic responses. The Word Cluster Instrument appeals most to Green and Gold personalities and attracts more logical and analytical responses.
Keywords: psychological tests; educational evaluation; personality; educational tests and measurements; personality psychology; quantitative psychology